Nilai-nilai Ketawadhuan dalam Tradisi Pesantren Ar-Risalah Bandung untuk Pengembangan Kultur Religius Sekolah - Mungaran, Muhammad Alif Anugrah; Hermawan, Wawan; Fakhruddin, Agus (IAIN Ponorogo, 2023)
Nowadays the religious culture in schools is starting to fade, one of which is regarding the fading of the school's religious culture in the form of humility which is marked by the emergence of the phenomenon of students committing acts of violence against teachers because they do not accept being reprimanded for their actions. In another phenomenon, it was found that students did not respect the teacher during the learning process. This research was conducted at the Ar-risalah Islamic boarding school in Bandung with the aim of describing how the values of laughter in the pesantren tradition are to be developed in the school's religious culture. This research is very important to neutralize humble attitude in public schools so that it becomes a positive tradition. This research uses a descriptive qualitative approach with a case study method. To obtain detailed information about the tradition of the values of humility in Islamic boarding schools, researchers used participatory observation. Data were collected from observations, interviews and documentation of pesantren leaders, teachers, santri supervisors and santri. The results of the study show that the values of humility are practiced in various forms in the daily life of students and each contains a basis and meaning based on Islamic teaching sources so that they can be adapted to public schools in developing a school religious culture in the form of students not leaving class or gathering before the teacher comes out first, students are accustomed to kissing the teacher's hand, students stand up and bow their heads. When a teacher wants to pass, students invite the teacher to lead first, and students respect the teacher.